Efisiensi Produksi Usaha Peternakan Domba di Desa Cibunian Kecamatan Pamijahan Kabupaten Bogor - L Cyrilla; Z Moesa; S M.P. Putri (Media Peternakan, 2010)
Sheep farming is a potential livestock commodity for agricultural development in the Country, but most of the farmers are not able to manage the farm effectively, technically or economically. The aims of this study were: (1) to determine production factors that would influence the sheep production, (2) to analyze sheep farming production efficiency. This study held in Cibunian Village, Pamijahan Sub District, Bogor Regency, West Java. The data was analyzed using Cobb-Douglas production function for regression analysis. The result showed that there were four significant variables. The variables which have significant effect to the production are sum of ewe (X1), roughages consumption (X2), labour employed (X3), and farmer experience in sheep farm (D2). Based on elasticity analysis can be said that technically the number of ewe was already efficient but not economically, because the ratio MVP/MIC of ewe was 1.15 so that farmer should increase the use of this production factor. The roughages consumption was already technically efficient, but economically it was not efficient, because the ratio MVP/MIC of roughages was less than one. It means that the use of this production factor needs to be reduced.   Keywords: sheep farm, Cobb-Douglas production function, technical efficiency, economical efficiency